Micro-, small- and medium-sized enterprises and their role in sustainable healthy diets in Ethiopia - de Brauw, Alan; Mengesha, Belay Terefe (International Food Policy Research Institute, 2025)
Ethiopia is working to transform its food system through a set of game changers that strive to change Ethiopia’s agricultural production patterns and to help improve consumption of under-consumed foods. The goal is to improve diet quality for Ethiopian consumers and households, which can only take place if consumers are more aware of what types of food to eat and if production of certain types of food can expand.